Peranan Komunikasi Publik pada Partai Pengusung Pilkada 2024 Kabupaten Bogor (Studi Terhadap Pasangan No 1 Rudy Susmanto dan Ade Ruhandi) - Gyarani, Anggita; Rifqi, Jauhar; Putranto, Algooth (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
According to the 2024 election commission (election committee) bogor 2024, the winner is the ruhandi no. 1 Rudy susmanto-ade ruhandi, with the 1,559,328 electory-musyafaur rahman with an issue of 559,453. Before the election was held on Wednesday, November 27, 2024, to search out sympathizers for voters, efforts have been made by both sides. A campaign through social media is being carried out to convince voters to make their choice. As the campaign is carried out, the winning couple select more social media campaigns asa form of public communication, while the campaign through mass mobilization is carried out by both prospective couples but higher levels of intensity by the number 1. Rudy susmanto's victory was also affected by images or self-image made public where previous periods had been DPRD's chairman with his very strong integrity character and his firmness for adherence to the prevailing rules. Besides which he created and operated programs that sided with the interests of many. This consistent value makes values a personal plus profile which is also an important aspect for affecting people to make choices during the election. The victory of the 1 Rudy susmanto-jaro ade was also the result of the powerful, dominant and effective party machine with the full 14 parties supporting the 18. The largest party carried by the number one in line rususmanto-jaro ade is senses and golkar. Bogor district's mobility was awarded 12 seats of parliament, while golkar was seven. In the meantime, the party of gerindra and golkar has become a coalition party in sthe 2024 presidential election, which is also a factor in the win of the number 1 group.